George Washington's socks - Woodruff, Elvira (New York : Scholastic, 1993)
In the midst of a backyard campout, ten-year-old Matt and four other children find themselves transported back to the time of George Washington and the American Revolution, where they begin to live out American history firsthand and learn the sober realities of war.
"An Apple paperback."
Reprint. Originally published: 1991.
840
Accelerated Reader AR
Keywords: Washington, George, -- 1732-1799 -- Juvenile fiction; Time travel -- Juvenile fiction; United States -- History -- Revolution, 1775-1783 -- Juvenile fiction; Historical fiction; War fiction